2015
DOI: 10.1186/s13014-015-0488-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual, irritative, and voiding outcomes, following stereotactic body radiation therapy for prostate cancer

Abstract: BackgroundUrinary symptoms and sexual dysfunction are the two most common complaints following prostate radiotherapy. The impact of hypofractionated treatment on sexual function, irritative symptoms, and voiding symptoms has not been determined within the same patient population. Here we present our institutional data on sexual function, voiding function, irritative symptoms, and treatment response following SBRT.MethodsThis retrospective analysis includes 102 non-metastatic patients treated with SBRT at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Furthermore, LUTS in men treated with radiation therapy are significantly worse compared to those who receive prostatectomy alone [10]. Moreover, LUTS are also reported to persist for years after completion of radiation treatment [11,12]. In some cases, LUTS may recur or worsen months or years following radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LUTS in men treated with radiation therapy are significantly worse compared to those who receive prostatectomy alone [10]. Moreover, LUTS are also reported to persist for years after completion of radiation treatment [11,12]. In some cases, LUTS may recur or worsen months or years following radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, little improvement is seen in ED percentages over time. 11 Occasionally, these numbers stabilize or return to baseline. This was demonstrated by Siglin et al, 16 who followed several domains of sexual function in men who had undergone EBRT.…”
Section: Radiation Therapymentioning
confidence: 99%
“…The reported incidence ranges from 10% to 60%. [10][11][12] Several animal model studies have examined stereotactic body radiation therapy to the prostate, neurovascular bundles, and penile bulb. Nolan et al 13 showed that prostatic irradiation caused arterial damage (specifically, altered internal pudendal arterial tone) and decreased motor function in the pudendal nerve (from axonal degeneration and loss).…”
Section: Radiation Therapymentioning
confidence: 99%
“…Combining IMRT, hypofractionation, and a simultaneous integrated boost has been shown to be a safe and effective treatment option for prostate cancer patients. Prostate cancer patients treated with Cyberknife stereotactic body RT exhibited minimal acute toxicity 31 . Prostate-specific antigen response, toxicity, preservation of erectile function, and improvement in urinary function compare favorably to data presented following radical prostatectomy, brachytherapy, or conventional external beam RT 32 …”
Section: History Of Ed Treatmentmentioning
confidence: 75%